EFFECT OF CAPITAL STRUCTURE AND PROFITABILITY ON FIRM VALUE:CASE STUDY OF THE PROPERTY AND REAL ESTATE SUBSECTOR IN INDONESIA - Een Suhaenah; Mirawati Firdaus; Ramos Turnip; Sri Hartatik; Helin G Yudawisastra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to determine the effect of capital structure and profitability on firm value in the property and real estate sub-sector in Indonesia. The research data was taken from the 2016-2019 financial statements. The sampling technique uses purposive random sampling. From 54 property and real estate sub-sector companies listed on the Indonesia Stock Exchange, 37 samples were taken that met the criteria. This study uses multiple linear regression analysis with panel data. Empirical results show that capital structure and return on assets influence firm value. Based on the model used, the variable has a 40.27% contribution, and the rest of the variables are not examined.